Intra-thoracic injuries associated with cardiopulmonary resuscitation – Frequent and serious. (June 2016) - Ihnát Rudinská, Lucia; Hejna, Petr; Ihnát, Peter; Tomášková, Hana; Smatanová, Margita; Dvořáček, Igor
Abstract: Aim of the study: The aim of the study was to evaluate prevalence, seriousness and risk factors of intra-thoracic injuries (ITI) injuries associated with CPR in non-survivors after out-of-hospital cardiac arrest. Methods: This was a prospective forensic autopsy cohort study conducted in a single institution. Pathologists recorded autopsy data using standardized protocol which contained data from external and internal examination of the body focused on ITI. Results: In total, 80 persons were included in this study. CPR-associated injuries were found in 93.7% of cases; majority of injuries were skeletal chest fractures (rib fractures in 73.7%, sternal fractures in 66.3%). ITI were identified in 41.2% of cases. Contusion of at least one lung lobe was found in 31.2%, lung laceration in 2.5%, and hemothorax in 5.0% of cases. Transmural heart contusion was identified in 17.5% of cases; hemopericard on the grounds of right atrium rupture of aortic rupture was revealed in 8.7% of cases. Risk factor analysis did not show any statistically significant correlation between ITI and any of general data (age, gender, BMI, cause of death, season of the year or location where the body was found) or CPR specifications (type and duration of CPR, manner of chest compressions). A strong correlation between ITI and skeletal chest fractures was proven. Conclusion: ITI present frequent and serious complications of unsuccessful CPR. ITI could contribute to the death only provided the fact that ROSC had been achieved. Correct performance of chest compressions according to guidelines is the best way to avoid ITI.